VOCABULARY AS CORE ELEMENT IN FOREIGN LANGUAGE LEARNING - Shadmanbekova Kamola Abdulazizovna (Bright Mind Publishing, 2025)
Today, it aims to improve the quality of learning and make language acquisition more effective. Vocabulary is central to speaking skills and overall language use. This article discusses why teaching vocabulary is the most important part of learning in foreign language.
Keywords: Educational process, knowledge, lexical skills, learning efficiency, vocabulary acquisition, active vocabulary minimum.